Participatory assessment of management and biosecurity practices of smallholder pig farms in North East India - Singh, Mahak; Pongenere, Nungshitula; Mollier, R. T.; Patton, R. N.; Yadav, Rekha; Katiyar, Rahul; Jaiswal, Priyanka; Bhattacharjee, M.; Kalita, H.; Mishra, V. K. (Frontiers in Veterinary Science, 2023)
The present study was aimed at describing the pig production system, farm management, pig movement and existing biosecurity level of small-holders pig production system in North East India. A cross-sectional survey of 1000 pig producers in four districts (two urban and two rural) in core pig producing region of India, where ASF occurrence had been reported, was conducted. Mean pig population was significantly (p < 0.05) higher in urban districts. In urban districts, the most of the pig houses were isolated but located on roadside, while in rural districts, commune pig houses along the road side were more common. The majority of the respondent purchased (91%) or sold (60%) the pigs during past 12 months. Swill feeding was common in entire study area. Majority of the respondent (80%) in rural districts were unaware of ASF. Significant pig trade of live pigs and pork products was observed in urban district. In case of on-farm biosecurity measures, only 6.9% of respondents had fencing of pig farm, 99.3% did not have provision of footbath and only 17.2% of the respondents restricted the visitors' access to pig farm. The study revealed that pig production system is dominated by smallholding units with frequent introduction or exit of pigs along with poor on-farm biosecurity measures. With the current level of farm management and biosecurity practices, smallholder pig farmers are at increased risk of ASF and other contagious diseases.